A STUDY ON WORKERS PARTICIPATION IN KCP LIMITED IN CHENNAI - DR. A. KAVITHA, DR. M. ALAGUTHANKAMANI (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The project has been carried out at KCP LIMITED, on the title “A STUDY ON WORKERS PARTICIPATION IN KCP LIMITED”. This study helps to find out the workers interest and challenges towards the environment. This study helps the management to know the workers participation to improve the production & profit in KCP Limited. This survey helps to find out the effectiveness of training which leads to the workers skills & knowledge. This study helps to improve the cordial relationship between the workers and management towards the job. This study will helps to analyzing the suggestion of the workers, to the organization in their point of view. The type of research design is descriptive. The sample size is 100. The primary data required for the project work have been collected from the employees. The secondary data was generated from company manual, records, various websites, bulletins, etc. Various statistical tools such as Percentage Analysis, Chi-Square Test, Weighted Average Method have been applied for testing the reliability of the data. After the analysis, findings of the study and relevant suggestions have been provided to the management. Hence it can be concluded that the study has helped to identify the worker participation level of employees in KCP Ltd.